Art in anime : the creative quest as theme and metaphor - Cavallaro, Dani. (Jefferson, N.C. : McFarland & Company, Inc., 2012)
"This critical study explores anime's relationship with art from a twofold perspective. Drawing from categories as varied as romance, comedy, slice of life drama, science fiction, bildungsroman, and school drama, it examines anime's representation of characters pursuing diverse artistic activities and related aesthetic visions, focusing closely on the concepts of creativity, talent, expressivity and experimentation"--Provided by publisher.
Preface -- 1. Cultural perspectives -- 2. The search for a language -- 3. Mythyopoeia -- 4. Performance and visuality -- Filmography -- Appendix: Japanese art periods timeline -- Bibliography -- Index.
Includes bibliographical references (pages 225-230), filmography and index.
English.
eBooks on EBSCOhost
Keywords: Animated films -- Japan -- Themes, motives; Art and motion pictures -- Japan; Creation (Literary, artistic, etc.) in motion pictures; Art et cinéma -- Japon; PERFORMING ARTS -- Reference; Animated films -- Themes, motives; Art and motion pictures; Creation (Literary, artistic, etc.) in motion pictures; Japan; Kunstproduktion; Zeichentrickfilm; Japan